2016
DOI: 10.3895/rbqv.v8n2.3829
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre qualidade de vida e trabalho: a percepção de estudantes de graduação em enfermagem

Abstract: OBJETIVO: Avaliar a associação entre baixa percepção do nível de qualidade de vida (QV) e trabalho entre estudantes de graduação em enfermagem.MÉTODOS: Estudo analítico e transversal entre estudantes de uma instituição de ensino de Minas Gerais. Delineou-se a amostra em 312 pessoas, favorecendo a representatividade populacional. Utilizaram-se para coleta de dados: WHOQOL-Bref, Critério de Classificação Econômica Brasil e questionário condições demográficas, socioeconômicas, de saúde, discentes e hábitos de vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…For the quality of life data, there was a decrease in scores for the physical, psychological and environment domains. A study with 351 nursing students showed similar results, with low perception of quality of life for the same domains identified in this study, as well as for the domain related to social relationships (21) .…”
Section: Discussionsupporting
confidence: 81%
“…For the quality of life data, there was a decrease in scores for the physical, psychological and environment domains. A study with 351 nursing students showed similar results, with low perception of quality of life for the same domains identified in this study, as well as for the domain related to social relationships (21) .…”
Section: Discussionsupporting
confidence: 81%
“…Destaca-se que na eliminação manual dos artigos (leitura dos resumos e textos completos), os textos foram eliminados em virtude dos seguintes critérios de exclusão: tipo de estudo (31); população (146); e temática (292). FRACOLLI, 2016;GONÇALVES et al, 2016;BALBÉ et al, 2016;NUNES;MASCARENHAS, 2016;CORRÊA et al, 2017), percebeu-se uma incipiência de pesquisas com um olhar mais específico para a classe docente, tanto na realidade brasileira quanto internacional.…”
Section: Resultsunclassified
“…Na literatura brasileira, é crescente a realização de investigações sobre a temática QV com foco em diferentes populações, como crianças (MARTINI; PADOVANI; PEROSA, 2016), enfermeiros (GOMES; MENDES; FRACOLLI, 2016), magistrados da justiça do trabalho (ALVES, 2015), estudantes (GONÇALVES et al, 2016), pacientes (CORRÊA et al, 2017, policiais militares (RODRIGUES; OLIVEIRA; SILVA, 2015), idosos (BALBÉ et al, 2016) e bancários (NUNES; MASCARENHAS, 2016). Dentre estes diversos estudos, volta-se o olhar para as investigações com foco no grupo de professores da Educação Básica, questionando-se que tipo de pesquisas tem sido conduzidas e o quanto estas têm sido conclusivas na análise da QV desta classe de trabalhadores.…”
Section: Palabras-claveunclassified
“…That is why it is so difficult to access, because it is not easy to create or change habits, since they happen from the inside out and not from the outside in. Involving the reptilian is the limbic, which is the emotional part responsible for long‐term memories 7 …”
Section: Competencymentioning
confidence: 99%
“…This is largely responsible for our emotions and spontaneous social behavior. It is also the seat of deep memory 7 …”
Section: Competencymentioning
confidence: 99%